Automatic Integration of Clinical and Genetic Data Using cBioPortal...18th World Congress of Medical and Health Informatics, MedInfo 2021 - One World, One Health – Global Partnership for Digital Innovation, 2-4 October, 2021. - Brunner, Mauricio; Mullen, Lucas; Jauk, Federico; Oliver, Javier; Cayol, Federico; Minata, José; Herrera, Victor; Pavicic, Walter; Luna, Daniel; Risk, Marcelo; Rivello, Hernan Garcia; Benitez, Sonia (Studies in Health Technology & Informatics, 2022)
Precision medicine seeks to improve the prevention, diagnosis and treatment of patients based on genetic characteristics unique to each person. In oncology, therapeutic decisions have been established based on the genomic characteristics of each patient's tumor. Data integration is key for the successful implementation of precision medicine since it is necessary for both studying a large volume of data from different sources and working with an interdisciplinary and translational vision. In this work, a bioinformatic process was successfully implemented that allows the integration of patients' genomic data, from two molecular biology laboratories, with their clinical data provided by their electronic medical records. For this, the REDCap data capture software, the cBioPortal visualization and analysis software, and a computer tool developed to automate the processing and annotation of the information in REDCap were used to be included in cBioPortal, for the "Map of Tumor Genomic Actionability of Argentina" project.